2015
DOI: 10.1117/1.oe.54.1.015102
|View full text |Cite
|
Sign up to set email alerts
|

Direct design approach to calculate a two-surface lens with an entrance pupil for application in wide field-of-view imaging

Abstract: Abstract. In this work, a multifields optical design method aiming to calculate two high-order aspheric lens profiles with an embedded entrance pupil is proposed. This direct design algorithm is capable of partially coupling more than three ray bundles that enter the same pupil with only two surfaces. Both infinite and finite conjugate objectives can be designed with this approach. Additional constraints such as surface continuity and smoothness are taken into account to calculate smooth and accurate surface c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…While manufacturability has often constrained optical elements to have rotational invariance, the emerging field of freeform optics leverages more complex curvatures to enable novel functionalities and simplified compound optical systems 1 4 . These elements have been shown to be capable of correcting aberrations 3 , off-axis imaging 4 , expanding field of view 5 , and increasing depth of field 6 . Recent interest in freeform optics has been driven by potential applications in near-eye displays 7 , 8 as well as compact optical systems for medical, aerospace, and mobile devices where there are stringent constraints on the size and weight of the optical package 9 .…”
Section: Introductionmentioning
confidence: 99%
“…While manufacturability has often constrained optical elements to have rotational invariance, the emerging field of freeform optics leverages more complex curvatures to enable novel functionalities and simplified compound optical systems 1 4 . These elements have been shown to be capable of correcting aberrations 3 , off-axis imaging 4 , expanding field of view 5 , and increasing depth of field 6 . Recent interest in freeform optics has been driven by potential applications in near-eye displays 7 , 8 as well as compact optical systems for medical, aerospace, and mobile devices where there are stringent constraints on the size and weight of the optical package 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Originally, the multi-fields direct design method was proposed for two on-axis refractive freeform surfaces in imaging lens design with an incorporated entrance pupil 20,21 . In this work, it is further extended to solve a tailored imaging problem for off-axis mirror system.…”
Section: Multi-fields Design Methods To Calculate Two Off-axis Mirrorsmentioning
confidence: 99%
“…Thanks to our Deep Proton Writing [4] and Ultraprecision Diamond Tooling technologies, we can process optical components to feature extreme optical quality finish, high-aspect ratio structures and absolute freeform shapes [5,6]. Next to their obvious use non-imaging applications, we have recently shown that freeform optics also hold great potential for imaging applications [7,8]. For sub-micrometer features, we make use of 3D direct laser writing, based on two-photon photopolymerization using femtosecond laser pulses [9].…”
Section: Introductionmentioning
confidence: 97%